Influence of Physical School Environment on Students’ Learning Motivation in Public Secondary Schools in Plateau State - Tsoho Aliyu Abraham (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
The physical school environment plays a critical role in shaping students’ learning experiences and academic behaviour. A conducive learning environment characterized by adequate classrooms, proper ventilation, furniture, lighting, sanitation facilities, and safety measures enhances students’ motivation and participation in academic activities. However, many public secondary schools in Nigeria continue to experience poor infrastructural conditions that negatively affect students’ interest in learning. This study examined the influence of physical school environment on students’ learning motivation in public secondary schools in Plateau State, Nigeria. The study adopted a descriptive survey research design. The population comprised all students and teachers in public secondary schools in Plateau State. A sample of 300 respondents was selected using stratified and simple random sampling techniques. Data were collected using a structured questionnaire titled Physical School Environment and Learning Motivation Questionnaire (PSELMQ). The instrument was validated by experts in educational management and measurement and evaluation. A Cronbach Alpha reliability coefficient of 0.84 was obtained. Mean and standard deviation were used to answer the research questions, while chi-square statistics were used to test the hypotheses at 0.05 level of significance. Findings revealed that classroom condition, school sanitation, availability of instructional facilities, and school safety significantly influenced students’ learning motivation. The study concluded that a conducive physical school environment promotes students’ interest, participation, and engagement in learning activities. The study recommended improved funding for school infrastructure and regular maintenance of school facilities.